Machines and their vital beats: for a sensu lato cinema (Significação: Journal of Audiovisual Culture, 2021)
As from Arlindo Machado’s readings of Gilbert Simondon, back in the 1990s, we revise this author to explore his thoughts on imagination, invention and the complex net of relationships between machines and humans, in order to examine the practice of cinematography and its images.